Analisis Pengaruh Parkir Pada Badan Jalan Terhadap Kinerja Jalan Satu Arah (Studi Kasus : Jl. CengkehKec Kota Masohi): (STUDI KASUS : JL. CENGKEH KEC. KOTA MASOHI) - Marisa Wakano; Amaheka, Sammy G. M.; Metekohy, Juliet Grace (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
This study aims to analyze the impact of parking on the roadway on the performance of one-way streets, using the case study of Cengkeh Street in Masohi City District. Parking on the roadway is one of the factors contributing to the decline in road performance, especially on road segments that connect to economic activities, such as shopping centers and markets. The issues raised include reduced road capacity, decreased vehicle speed, and increased saturation degree due to parking on the roadway. The methodology used in this study involves a quantitative approach, collecting primary data through direct surveys and analysis using the Indonesian Road Capacity Manual (MKJI) 1997. The results show that the highest average daily traffic occurs on Sundays with 539 vehicles per hour. Parking on the roadway significantly affects road performance. Traffic volume increases when parking appears on the road, while road capacity decreases from normal conditions. The road capacity with parking on the road is 1,253.26 passenger car units per hour and 2,610.96 passenger car units per hour without parking on the road. The degree of saturation also significantly increases, reaching 0.43 in conditions with parking, with road service level up to level B, approaching the maximum road capacity limit. Parking characteristics show that the highest parking volume occurs on Tuesday from 10:00 AM to 12:00 PM WIT, with a high accumulation of vehicles on both sides of the road. This study provides recommendations for rearranging the parking system, implementing parking bans in certain zones, and optimizing parking spaces off the road to improve traffic performance. Keywords: Parking, performance, capacity, degree of saturation, level of road service